Aβ-mediated nuclear pore complex dysfunction in a mouse model of alzheimer's disease - Vibhavari, Bansal (Nanyang Technological University, 2023)
The nuclear pore complex (NPC) is a vital component of the nuclear envelope that regulates multiple processes including nucleocytoplasmic shuttling, chromosome organisation, and transcriptional regulation. While gradual loss of NPCs occurs in neurons during ageing, further dysregulation has been reported in different dementias. Here, I show evidence that Aβ expression that is associated with Alzheimer’s disease (AD) results in the loss of NPCs in neuronal nuclei in a mouse model of AD. The loss of NPCs and the nucleoporin subunits can be detected at early stages of the disease, and result in a degraded nuclear permeability barrier, causing defective subcellular compartmentalization of proteins, and impaired active import. Because of this NPC dysfunction, AD neurons become sensitised to inflammation-induced necroptosis – a cell death pathway dependent on nucleocytoplasmic shutting. Collectively, my results suggest that an Aβ-driven mechanism is responsible for NPC damage in AD neurons, with potentially severe consequences for neuronal viability.